Cavotricuspid isthmus ablation using ablation index in typical right atrial flutter. (25th September 2019) - Zhang, Tao; Wang, Yunlong; Han, Zhihong; Zhao, Hua; Liang, Zhuo; Wang, Ye; Wu, Yongquan; Ren, Xuejun
Abstract: Background: Ablation index (AI) has been evaluated as guidance quality marker for pulmonary vein isolation, but not for linear ablation of the cavotricuspid isthmus (CTI) for typical right atrial flutter (AFL). We thus studied the feasibility and effectiveness of AI‐guided CTI for AFL. Methods: Procedural and 6‐month outcomes of ablation for AFL were retrospectively compared between consecutive patients undergoing either AI‐guided ablation of CTI (n = 43; AI target of 500 for anterior 2/3 segments and 400 for posterior 1/3 segments) or contact force (CF)‐guided ablation (n = 42) at a single center. Each Visitag dataset from all patients in each group was analyzed. Results: AI guidance vs CF guidance was associated with: higher first‐pass conduction block of CTI (93.0% vs 76.2%, P  = .03) with similar ablation time; similar acute spontaneous CTI reconnection 2.3% vs 9.5%, P  = .343); fewer radiofrequency (RF) applications (10.1 ± 2.8 vs 11.5 ± 3.0, P  = .031) needed to achieve CTI directional block; significantly higher mean ablation time, impedance drop, force time integral and AI and similar mean CF and power of each VisiTag point. One inguinal hematoma and one pseudoaneurysm developed in the AI and CF groups, respectively. Recurrent AFL was recorded in two (4.7%) AI‐group patients and four (9.5%) CF‐group patients ( P  = .650). Conclusion: AI‐guided ablation of CTI line for AFL appears feasible and effective with similar ablation time, fewer RF applications, a higher rate of first‐pass conduction block, and no additional complications.